Major Trends in Education - Irfan Irfan; Moch Subhan Syarif; Suyudi Suyudi; Fuad Abdul Baqi; Mutoharoh Mutoharoh (Universitas Pahlawan Tuanku Tambusai, 2026)
Education is a planned and organized effort aimed at developing human potential holistically, including intellectual, emotional, social, and moral aspects. Throughout the history of educational thought, various schools of thought have developed, each with its own characteristics regarding the nature of education, its goals, learning approaches, and the roles of educators and students. Traditional schools emphasize the importance of systematically and structured transmission of past values, culture, and knowledge. Progressivism, on the other hand, places greater emphasis on students' learning experiences, using a flexible and contextual approach tailored to the needs of the times. Meanwhile, existentialism allows individuals the freedom to determine the meaning and purpose of their education, while essentialism emphasizes the importance of mastering basic knowledge and essential skills as the foundation of education. Social reconstructionism views education as a means to bring about social change and create a better social order through innovation. The main findings. From this study indicate that no single school of education is entirely superior; rather, each has complementary strengths and limitations. Integrating various approaches from these schools is a more relevant strategy in addressing the complex challenges of modern education. Furthermore, it was found that current educational trends are moving toward a more adaptive, contextual, and learner-oriented approach without neglecting the importance of core values and knowledge structures. Theoretical implications of this study reinforce the importance of an eclectic approach in developing educational theory that is not tied to a particular school of thought. Practically, the results of this study provide recommendations for educators and education administrators to combine various learning approaches proportionally according to the needs of students and the context of the educational environment. Thus, education is expected to become more relevant, innovative, and responsive to the dynamics of change.